Association between Ocular Pseudoexfoliation and Sensorineural Hearing Loss. (17th April 2014) - Singham, Nandini Vijaya; Zahari, Mimiwati; Peyman, Mohammadreza; Prepageran, Narayanan; Subrayan, Visvaraja
Abstract : Background . Our study aimed to investigate an association between ocular pseudoexfoliation (PXF) and sensorineural hearing loss (SNHL) and to compare them with age and sex matched controls without pseudoexfoliation. Method . This was a case-control study of 123 patients which included 68 cases with PXF (at least one eye) and 55 controls without pseudoexfoliation. Pure-tone audiometry (PTA) was done for these patients at sound frequencies taken as important for speech comprehension, that is, 250 Hertz (Hz), 500 Hz, 1000 Hz, and 2000 Hz. Results . There were 41 patients with pseudoexfoliation syndrome (PXE) and 27 with pseudoexfoliative glaucoma (PXEG). The majority of patients with hearing loss (60%; n = 51 ) were PXF patients and the remaining 40% ( n = 34 ) were controls. Below average hearing thresholds were significantly higher in the pseudoexfoliation group compared to the control group (P = 0.01 ; odds ratio (OR), 3.00; 95% confidence interval (CI), 1.25–7.19). However, there was no significant difference in the mean hearing threshold levels between the three groups (PXE, PXEG, and controls) in either ear (ANOVA, right ear: P = 0.46 and left ear P = 0.36 ). Conclusion . Our study found an association between PXF and SNHL, confirming that PXF can involve organs in the body other than the eye.